2021
DOI: 10.1155/2021/5525547
|View full text |Cite
|
Sign up to set email alerts
|

The Epoxidized Vietnam Rubber Seed Oil as a Secondary Plasticizer/Thermal Stabilizer in PVC Processing

Abstract: The epoxidized rubber seed oil (EeRSO) was a mixture of epoxidized triglyceride, and epoxidized methyl ester of free fatty acids was used as a secondary plasticizer for PVC. An increase in tensile properties was observed by substituting the 10 phr DOP plasticizer with the EeRSO in PVC formulation. A leaching test was performed in five media to evaluate the plasticizing effect. The sample weight increased slightly after soaking in water and 30 wt.% acetic solution, decreased slightly in 10 wt.% KOH solution, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…90 Similarly, in different studies, epoxidized rubber seed oil was found to act as a primary plasticizer for PVC to improve its migration, extraction, and volatilization characteristics and contribute to its thermal stability. 91 Additionally, researchers are becoming increasingly interested in eco-friendly plasticizers that work well with different materials, which fits the worldwide move towards biodegradable polymers. 92 Although phthalate esters are widely used, they are harmful to human health, and thus it is essential to find alternative options.…”
Section: Chemical Modification Of Vegetable Oils (Vos) Into 3d-printa...mentioning
confidence: 99%
“…90 Similarly, in different studies, epoxidized rubber seed oil was found to act as a primary plasticizer for PVC to improve its migration, extraction, and volatilization characteristics and contribute to its thermal stability. 91 Additionally, researchers are becoming increasingly interested in eco-friendly plasticizers that work well with different materials, which fits the worldwide move towards biodegradable polymers. 92 Although phthalate esters are widely used, they are harmful to human health, and thus it is essential to find alternative options.…”
Section: Chemical Modification Of Vegetable Oils (Vos) Into 3d-printa...mentioning
confidence: 99%
“…While monitoring the weight changes of a sample soaked in different liquids, there are two possible observations: a) weight increase when small molecules of the liquid diffuse into the polymer matrix, and b) weight reduction when some additives (in this case plasticizer) are extracted from the sample. These two phenomena can occur simultaneously or separately 49 . When using n-hexane in migration studies, the extraction of plasticizer dominates, so the sample weight decreases 50,51 .…”
Section: Migration Studiesmentioning
confidence: 99%
“…However, their effectiveness is still mild, so a co-stabilizer (secondary thermal stabilizer) is needed to increase their efficacy [ 28 ]. Epoxidized vegetable oil, prepared by epoxidizing the unsaturated part of vegetable oil, is one of the most popular groups of co-stabilizers [ 29 ]. The commonly used epoxidized vegetable oil in the PVC industry is epoxidized soybean oil (ESBO) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used epoxidized vegetable oil in the PVC industry is epoxidized soybean oil (ESBO) [ 30 ]. Other vegetable oils, such as sunflower oil [ [31] , [32] , [33] ], rubber seed oil [ 29 , 34 ], and silkworm pupae oil [ 35 ] have also been studied in epoxidized forms to stabilize PVC. KSO contains a large amount of unsaturated fraction, making it very promising for use as a raw material for producing epoxy-based co-stabilizers.…”
Section: Introductionmentioning
confidence: 99%